Disclosure of the internal transport phenomena in an air-cooled proton exchange membrane fuel cell—part III: Performance research based on qualitative comparisons between modeling and experimental results. (29th January 2022) - Pan, R.; Hu, M.
Abstract: The validation of a computational fluid dynamics model for a proton exchange membrane fuel cell (PEMFC) is normally conducted by the experimental I–V performance curve. However, it seems this method is not solid enough. In the meantime, it's difficult to conduct the item-to-item quantitative comparisons between the internal distributions acquired from numerical and testing results. Therefore, in this paper, as the first attempt, qualitative comparisons between the modeling and experimental results are conducted based on the three important parameters of an air-cooled PEMFC (air stoichiometric ratio, air relative humidity, cathode flow field design) to explore the trends of the related fuel cell I–V performance curves and internal resistances. The internal resistances are tested using the EIS technique and differentiated by an equivalent circuit model. Conclusions show that the qualitative comparisons between the numerical and testing results support each other well and new results are found based on the comparisons. Finally, discussions on the sensitivity based on the experimental EIS results are conducted to explore the response degree of the total resistance to the air stoichiometric ratio, the air relative humidity and the cathode flow field design. Highlights: Qualitative comparisons between modeling and testing results support each other. Proton transport is the dominant factor affecting the reaction rate and resistance. Sensitivity is defined to compare different parametric series. Air relative humidity could lead to "Strong" sensitivity in the case of dry air. Air stoichiometric ratio has the strongest effect most of the time.